Comprehensive multimodality characterization of hemodynamically significant and non-significant coronary lesions using invasive and noninvasive measures - Engel, Leif-Christopher; Landmesser, Ulf; Abdelwahed, Youssef S.; Jaguszewski, Milosz; Gigengack, Kevin; Wurster, Thomas-Heinrich; Skurk, Carsten; Manes, Costantina; Schuster, Andreas; Noutsias, Michel; Hamm, Bernd; Botnar, Rene M.; et al. (PLoS ONE, 2020)
Background There is limited knowledge about morphological molecular-imaging-derived parameters to further characterize hemodynamically relevant coronary lesions. Objective The aim of this study was to describe and differentiate specific parameters between hemodynamically significant and non-significant coronary lesions using various invasive and noninvasive measures. Methods This clinical study analyzed patients with symptoms suggestive of coronary artery disease (CAD) who underwent native T1-weighted CMR and gadofosveset-enhanced CMR as well as invasive coronary angiography. OCT of the culprit vessel to determine the plaque type was performed in a subset of patients. Functional relevance of all lesions was examined using quantitative flow reserve (QFR-angiography). Hemodynamically significant lesions were defined as lesions with a QFR <0.8. Signal intensity (contrast-to-noise ratios; CNRs) on native T1-weighted CMR and gadofosveset-enhanced CMR was defined as a measure for intraplaque hemorrhage and endothelial permeability, respectively. Results Overall 29 coronary segments from 14 patients were examined. Segments containing lesions with a QFR <0.8 (n = 9) were associated with significantly higher signal enhancement on Gadofosveset-enhanced CMR as compared to segments containing a lesions without significant stenosis (lesion-QFR>0.8; n = 19) (5.32 (4.47–7.02) vs. 2.42 (1.04–5.11); p = 0.042). No differences in signal enhancement were seen on native T1-weighted CMR (2.2 (0.68–6.75) vs. 2.09 (0.91–6.57), p = 0.412). 66.7% (4 out of 6) of all vulnerable plaque and 33.3% (2 out of 6) of all non-vulnerable plaque (fibroatheroma) as assessed by OCT were hemodynamically significant lesions. Conclusion The findings of this pilot study suggest that signal enhancement on albumin-binding probe-enhanced CMR but not on T1-weighted CMR is associated with hemodynamically relevant coronary lesions.
CRIS-Team Scopus Importer:2023-03-08